Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0014-5793(00)01364-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized phospholipids activate PPARα in a phospholipase A2‐dependent manner

Abstract: The peroxisome proliferator-activated receptor K K (PPARK K) is a transcription factor belonging to the PPAR subfamily of nuclear receptors. Fatty acids and eicosanoids are natural PPARK K ligands. Here, we show using transient transfection assays that oxidized (oxLDL) but not native lowdensity lipoproteins (LDL) dose-dependently activate PPARK K in endothelial cells without affecting PPARK K protein expression. Fractioning of oxLDL lipids followed by transactivation experiments demonstrated that the oxidized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(113 citation statements)
references
References 41 publications
4
106
2
1
Order By: Relevance
“…Given that LysoPC is the major product of PON1 hydrolytic activity in the presence of oxLDL and that LysoPC can stimulate the PPARc-LXRa-ABCA1 pathway, this strengthens the notion that oxLDL-PON1 promotes cholesterol efflux by the activation of the PPARc-LXRa-ABCA1 pathway in J774 macrophages and that this effect is due to the LysoPC formed by the hydrolytic activity of PON1. Previous study of Delerive et al showed that oxLDL induced the activation of PPARa on human coronary endothelial cells in a phospholipase A2-dependent manner [53]. In the present study, we did not investigate the effect of oxLDL-PON1 on PPARa expression on macrophages; however, our results confirm that PON1, due to its PLA2-like activity, hydrolyzes oxLDL to induce the activation of PPARc.…”
Section: Discussioncontrasting
confidence: 47%
“…Given that LysoPC is the major product of PON1 hydrolytic activity in the presence of oxLDL and that LysoPC can stimulate the PPARc-LXRa-ABCA1 pathway, this strengthens the notion that oxLDL-PON1 promotes cholesterol efflux by the activation of the PPARc-LXRa-ABCA1 pathway in J774 macrophages and that this effect is due to the LysoPC formed by the hydrolytic activity of PON1. Previous study of Delerive et al showed that oxLDL induced the activation of PPARa on human coronary endothelial cells in a phospholipase A2-dependent manner [53]. In the present study, we did not investigate the effect of oxLDL-PON1 on PPARa expression on macrophages; however, our results confirm that PON1, due to its PLA2-like activity, hydrolyzes oxLDL to induce the activation of PPARc.…”
Section: Discussioncontrasting
confidence: 47%
“…4C). The oxidized molecules likely responsible for these effects have been identified as 9-and 13-HODE, both established PPAR␥ (27) and PPAR␣ activators (30). Such HODEs are released during LDL hydrolysis of LDL(Ϫ) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PPAR␣ LBD activation by HODE has been reported (30). To evaluate the extent of PPAR␣ activation by HODE and HpODE, cell-free displacement and cell-based LBD assays were performed.…”
Section: Fig 2 Lpl Treated Ldl(؊) Inhibits Nf B Activation and Incrmentioning
confidence: 99%
“…Alternatively, M-CSF-stimulated or adenovirus-transduced macrophages were incubated for 48 hours with 1 to 100 g/mL of human oxLDL prepared by complete CuSO 4 oxidation, as described (215.2Ϯ32 nmol peroxides/mg protein, 46Ϯ4 nmol TBARS/mg protein). 35 …”
Section: Culture and Adenoviral Transduction Of Bone Marrow-derived Mmentioning
confidence: 99%